NEW DATA ON BIOTIC EVENTS DURING THE SANTONIAN-CAMPANIAN TRANSITION: EVIDENCE FROM MICROPLANKTON FOSSILS OF THE RUSSIAN PACIFIC MARGIN - Vishnevskaya V.S.; Basov I.A. (My University, 2007)
The Albian–Cenomanian and Cenomanian–Turonian extinctions were among the most significant Cretaceous biotic events. The terminal Albian was marked by the last speciation outburst of the radiolarian genus Crolanium that became practically extinct in the early Cenomanian. The total diversity of the Cenomanian radiolarian assemblage was 75 species, which is two times lower as compared with that in the middle Albian. By the end of the Cenomanian, diversity of radiolarians increased to 140–150 species and became again two times lower during the Cenomanian–Turonian boundary period, when half of these species, representatives of the family Rotaformidae included, became extinct. Similar to the ammonoid species Schloenbachia with the massive shell, the heavily ornamented radiolarian genus Godia also disappeared at that time.
Keywords: Campanian; Santonian; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Кампанский; Mesozoic::Cretaceous::Upper::Santonian; Мезозой::Меловая::Верхний::Сантонский